2022
DOI: 10.3390/foods11131867
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Nattokinase-Enriched Fermented Soybean Foods: A Review

Abstract: With the dramatic increase in mortality of cardiovascular diseases (CVDs) caused by thrombus, this has sparked an interest in seeking more effective thrombolytic drugs or dietary nutriments. The dietary consumption of natto, a traditional Bacillus-fermented food (BFF), can reduce the risk of CVDs. Nattokinase (NK), a natural, safe, efficient and cost-effective thrombolytic enzyme, is the most bioactive ingredient in natto. NK has progressively been considered to have potentially beneficial cardiovascular effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 143 publications
(145 reference statements)
0
12
0
Order By: Relevance
“…Among them, the thrombolytic effects of (2), (3), and (4) are achieved through the activation of fibrinogen. 24,26 Treatment of thrombotic complications…”
Section: Anti-thrombosismentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, the thrombolytic effects of (2), (3), and (4) are achieved through the activation of fibrinogen. 24,26 Treatment of thrombotic complications…”
Section: Anti-thrombosismentioning
confidence: 99%
“…Researchers have studied crude extracts of NK and have shown that NK can effectively prevent or treat blood clots through direct or indirect routes and intervene in diseases such as hypertension, hyperglycemia, and liver cancer. [24][25][26][27][28] In addition, NK-producing strains not only produce NK when acting on different substrates but also give different properties to fermented foods depending on the fermentation substrate, such as an improvement of antioxidant activity and absorbability, and the production of polyphenolic compounds. 22,29,30 Therefore, safe strains with the ability to produce NK can also potentially develop functional foods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natto is a traditional soybean product fermented by Bacillus subtilis that contains various functional components, such as nattokinase (NK), vitamin K, isoflavones, superoxide dismutase, phospholipids, saponins, and linoleic acid [ 1 , 2 ]. Natto is a low-cost but high-nutrition product made using a simple procedure.…”
Section: Introductionmentioning
confidence: 99%
“…4 For these reasons, NK is considered a possible relevant drug that may be involved in the primary or secondary prevention of thrombotic diseases. 5 After the evaluation of the National Science Foundation in the United States of America, the general audience toward NK is increasing, and studies in vitro and in vivo are increasing too. 6 We here report current pieces of knowledge of NK actions.…”
mentioning
confidence: 99%